A question of uniformitarianism: Has the geological past become the key to humanity's future?. (March 2015) - Paul, Jonathan D.
Abstract: The acceptance of the Anthropocene as a new unit of geological time presents challenges for uniformitarian geologists. The principle of uniformitarianism, and relative merits of uniformitarian concepts in general, are subject to fierce debate. While the present may hold the key to the past, it is increasingly difficult to make accurate, credible, and useful inferences of future behaviour using the geological past as a guide. Complex projections on long (>100 years) timescales will never be completely accurate, as the actions of, an interactions within, human societies, will never be fully known. Global population growth and the consequences of industrial progress appeal more to a catastrophist, rather than a substantive uniformitarian, model. However, the quest for sustainability has led to a resurgence of interest in scrutinising the geological record to construct long-term solutions. Increasingly, a basic geological grounding is essential in multi-disciplinary studies that aim to offset or reduce deleterious anthropogenic impacts. The anthropogenic present must act as a filter through which the past is interpreted when searching for keys to the future.